Tata Kelola Persediaan Bahan Baku Usaha Djamoe Van Java untuk Meningkatkan Efisiensi Pembuatan Jamu - Mohamad Rifky Fahrian Hidayat; Sulaeman Miru; Syamsuddin Syamsuddin; Juliana Kadang (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Raw material inventory is unprocessed basic material provided by the company for later use in the company's production process. Raw materials are important in production companies. Limited or excess supplies of raw materials can be a problem for the company. A shortage of raw materials can result in problems with company activities, especially in the production process, while excess supplies of raw materials can lead to excessive costs in maintaining raw materials and the value of raw materials will decrease over time (Anista & Widiyastuti, 2016). The method used in this research is quantitative descriptive. According to Winartha (2006: 155), the quantitative descriptive method is analyzing, describing and summarizing various conditions and situations from various data in the form of numbers collected from the results of analysis and interviews or observations regarding the problems being studied that occur in the field. Based on the calculation results, the optimal quantity of raw material orders for the Djamoe Van Java business is 10 Kg. Based on the results of the research and discussion described previously, it can be concluded that to obtain optimal raw material inventory management for the Djamoe Van Java business, the quantity The economic purchase (EOQ) that the company must provide is 10 kg. The results of calculations that have been carried out in Total Inventory Cost (TIC) show that after implementing an appropriate and optimal inventory control system, the company can save costs of IDR 150,000. Companies should determine Reorder Points in carrying out raw material inventory control to anticipate possible delays in ordering raw materials.